Study of Buongiorno’s nanofluid model for flow due to stretching disks in presence of gyrotactic microorganisms - Yu-Ming Chu; Kamel Al-Khaled; Nargis Khan; M. Ijaz Khan; Sami Ullah Khan; Muhammad Sadiq Hashmi; Muhammad Azhar Iqbal; Iskander Tlili (Ain Shams Engineering Journal, 2021)
Owing to the widespread practical significances of nanoparticles in thermal engineering and industrial processes, scientists are devoted to explore the more fundamental thermal aspects of such nano-materials. Recently, the nanoparticles show extensive applications in heat transfer improvement, energy production, cooling and heating processes, refrigeration, thermal extrusion processes, thermoelectric devices, bio-medical applications like cancer treatment, brain tumors and many more. Moreover, the phenomenon of bioconvection utilize interesting applications in bio-technology, bio-fuels, enzymes, fertilizes etc. Keeping such motivations in mind, this research presents the bioconvection flow of nanofluid induced by two stretchable disks separated at confined distance. The Buongiorno nanofluid model is employed to examine the Brownian motion and thermophoresis aspects. The equations govern for the flow of the nanofluid, heat transfer; nanoparticles concentration and density of motile microorganisms’ fields are simplified with the help of similarity transformation. The resultant form of nonlinear equations is solved by using homotopy analysis method. The influence of significantly participating parameters on velocity, nanofluid temperature, concentration and density of motile microorganisms profiles are observed with relevant physical significances. The convergence of solution for velocity, temperature, concentration and motile microorganisms profiles are examined carefully. The simulations are compared with already declared numerical data and found a convincible accuracy. It is noticed that the temperature profile enhances up to specified range and then start decline due to larger values of values of Brownian motion and thermophoresis parameters. A dual nature of velocity profiles for higher the value of stretching parameter has been observed. The concentration profile declines with increasing Brownian motion constant and Lewis number. The motile microorganisms profile decreases due to enhancement of bio-convection Peclet number, Reynolds number and Schmidt number.